Position of arm and forearm, and elbow flexion during performance of the sculling technique: Technical recommendation versus actual performance - Lara Elena Gomes; Mônica de Oliveira Melo; Victor Wigner Tremea; Marcelo La Torre; Yumie Okuyama da Silva; Flávio de Souza Castro; Jefferson Fagundes Loss (Universidade Estadual Paulista (UNESP), 2014)
Sculling motion is a swimming technique executed in a vertical position with the head above the water's surface and, based on the technical recommendation, should be performed maintaining an elbow flexion angle of 90°, arms kept stationary while the forearms move. In order to verify if this recommendation is indeed realistic, the aim of this study was to describe the elbow flexion angle ant its angular velocity, linear speed and range of motion of the shoulder, elbow and wrist during the sculling motion. Data were calculated using three-dimensional kinematic process from underwater video images of ten athletes of synchronized swimming. The results indicate that the arm is relatively stationary and the forearm moves, which agrees with the technical recommendation. However, the elbow flexes and extends, which contradicts the technical recommendation. These findings should be considered when this action is practiced, especially in synchronized swimming, in which sculling motion is a fundamental technique.